Macaque Area V2/V3 Reorganization Following Homonymous Retinal Lesions - Keliris, Georgios A.; Shao, Yibin; Schmid, Michael C.; Augath, Mark; Logothetis, Nikos K.; Smirnakis, Stelios M. (Frontiers in Neuroscience, 2022)
In the adult visual system, topographic reorganization of the primary visual cortex (V1) after retinal lesions has been extensively investigated. In contrast, the plasticity of higher order extrastriate areas following retinal lesions is less well studied. Here, we used fMRI to study reorganization of visual areas V2/V3 following the induction of permanent, binocular, homonymous retinal lesions in 4 adult macaque monkeys. We found that the great majority of voxels that did not show visual modulation on the day of the lesion in the V2/V3 lesion projection zone (LPZ) demonstrated significant visual modulations 2 weeks later, and the mean modulation strength remained approximately stable thereafter for the duration of our observations (4-5 months). The distribution of eccentricities of visually modulated voxels inside the V2/V3 LPZ spanned a wider range post-lesion than pre-lesion, suggesting that neurons inside the LPZ reorganize by receiving input either from the foveal or the peripheral border of the LPZ, depending on proximity. Overall, we conclude that area V2/V3 of adult rhesus macaques displays a significant capacity for topographic reorganization following retinal lesions markedly exceeding the corresponding capacity of area V1.